PENGARUH PEMBERIAN EKSTRAK KULIT BUAH NANAS TERFERMENTASI MELALUI AIR MINUM TERHADAP KUALITAS FISIK DAGING AYAM KUB - K. Kautzardi; N.L.P. Sriyani; I.M. Nuriyasa (Fakultas Peternakan Universitas Udayana, 2025)
The physical quality of meat is a parameter of meat physical quality testing, which consists of acidity level (pH), Water Holding Capacity, Cooking Loss, and Drip Loss. This study aimed to determine the effect of administering fermented pineapple peel extract through drinking water on the physical meat quality of superior native chickens (KUB chickens) developed by the Indonesian Agency for Agricultural Research and Development (Balitbangtan). The research was conducted over 8 weeks using a completely randomized design (CRD) with 4 treatments and 5 replications, resulting in a total of 20 experimental units. Each experimental unit consisted of 3 two-week-old KUB chickens. The treatments were as follows: P0 = 0% fermented pineapple peel extract, P1 = 11% fermented pineapple peel extract, P2 = 12% fermented pineapple peel extract, and P3 = 13% fermented pineapple peel extract, administered through drinking water. The observed variables included pH (degree of acidity), water holding capacity, cooking loss, and raw meat loss. The results showed that administration of fermented pineapple peel extract at levels of 11%, 12%, and 13% through drinking water had no significant effect (P>0.05) on pH, water holding capacity, cooking loss, or raw meat loss. Based on these findings, it can be concluded that the administration of fermented pineapple peel extract at levels of 11%, 12%, and 13% through drinking water does not affect the physical meat quality of KUB chickens. ABSTRAK Kuialitas fisik daging meiruipakan parameiteir dari peinguijian kuialitas fisik daging yang teirdiri dari deirajat keiasaman (pH), Daya Ikat Air, Suisuit Masak, dan suisuit meintah. Peineilitian ini beirtuijuian uintuik meingeitahuii peingaruih peimbeirian eikstrak kuilit buiah nanas teirfeirmeintasi meilaluii air minuim teirhadap kuialitas fisik daging ayam kampuing uingguil balitbangtan. Peineilitian ini teilah dilaksanakan seilama 8 minggui, meingguinakan rancangan acak leingkap (RAL) deingan 4 peirlakuian dan 5 uilangan, seihingga teirdapat 20 uinit peircobaan. Seitiap uinit peircobaan beirisi 3 eikor ayam KUiB beiruimuir 2 minggui. Peirlakuian eikstrak kuilit buiah nanas teirfeirmeintasi meilaluii air minuim yaitui P0 = 0% eikstrak kuilit buiah nanas teirfeirmeintasi, P1 = 11% eikstrak kuilit buiah nanas teirfeirmeintasi, P2 = 12% eikstrak kuilit buiah nanas teirfeirmeintasi, P3 = 13% eikstrak kuilit buiah nanas teirfeirmeintasi. Variabeil yang diamati adalah deirajat keiasaman (pH), daya ikat air, suisuit masak, dan suisuit meintah. Hasil peineilitian meinuinjuikkan bahwa peimbeirian eikstrak kuilit buiah nanas teirfeirmeintasi pada leiveil 11%,12% dan 13% meilaluii air minuim tidak beirpeingaruih nyata (P>0,05) teirhadap variabeil deirajat keiasaman (pH), daya ikat air, suisuit masak, suisuit meintah. Beirdasarkan peineilitian ini dapat disimpuilkan bahwa peimbeirian eikstrak kuilit buiah nanas teirfeirmeintasi deingan leiveil 11%, 12% dan 13% meilaluii air minuim tidak beirpeingaruih teirhadap kuialitas fisik daging ayam KUiB.